TBHP/KI-Promoted Oxidative Cyclization of α-Aminoketones for One-Pot Synthesis of Substituted 2-Acyloxazoles - Zheng, Jiecheng; Zhu, Dali; Yang, Zhangyou; Chen, Huali; Wang, Wei; Gan, Lin Ling; Gan, Zongjie (Synthesis, 2023)
A metal-free and facile synthesis of substituted 2-acyloxazole derivatives from α-aminoketones was developed via a TBHP/KI-promoted oxidative cyclization. This procedure proceeded smoothly under mild conditions and a broad scope of 2-acyloxazoles were obtained in moderate to good yields.
Keywords: metal-free; TBHP/KI; 2-acyloxazole; oxidative cyclization